1990
DOI: 10.1007/bf01310510
|View full text |Cite
|
Sign up to set email alerts
|

Feline herpesvirus type 1 glycoproteins eliciting virus neutralizing and hemagglutination-inhibiting antibodies

Abstract: Monoclonal antibodies (MoAbs) to feline herpesvirus type 1 (FHV-1) were produced to identify the virus-specified immunogenic proteins. When antigens recognized by the MoAbs were investigated by immunoblot and immunoprecipitation assays using FHV-1-infected cell lysate, four groups of immunogenic proteins were identified. MoAbs directed against 60 kDa, 113 kDa, and 143 kDa/108 kDa glycoproteins had virus neutralizing activities, but those against 170 kDa protein did not. Furthermore, MoAbs to the 60 kDa glycopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
1

Year Published

1990
1990
1997
1997

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 8 publications
0
15
1
Order By: Relevance
“…3). However, the adhesion was not inhibited by MAbs 22F4 and 17C11 against FHV-1 gB and gC, respectively [7], when the MAbs were used as a control. These results indicated that FHV-1 gD might involve in restrictive adhesion between FHV-1 gD-expressing cells and cells susceptible to FHV-1 infection.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…3). However, the adhesion was not inhibited by MAbs 22F4 and 17C11 against FHV-1 gB and gC, respectively [7], when the MAbs were used as a control. These results indicated that FHV-1 gD might involve in restrictive adhesion between FHV-1 gD-expressing cells and cells susceptible to FHV-1 infection.…”
mentioning
confidence: 89%
“…FHV-1 genes encoding seven glycoproteins, gB, gC, gD, gG, gH, gI and gE, were identified [14,17,18,21,22]. With the use of monoclonal antibodies (MAbs) against FHV-1, we identified three kinds of glycoproteins, gB, gC, and gD which induce virusneutralizing (VN) antibodies [7]. Especially, some of the MAbs against FHV-1 gD had hemagglutination (HA)-inhibition (HI) and complement-independent VN activities, and the gD expressed in Sf9 cells or affinity-purified gD induced VN antibody in mouse [7,13].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As is typical of other herpesviruses, numerous FHV-1 glycoproteins are synthesized and then incorporated into membranes of infected cells and the virion envelope (Fargeaud et al, 1984;Maes et al, 1984;Limcumpao et al, 1990). These glycoproteins have been well characterized and are conserved among related herpesviruses.…”
Section: Introductionmentioning
confidence: 99%